Flow control in s-shaped air intake diffuser of gas turbine using proposed energy promoters - Jessam, R.A. (EDP Sciences, 2017)
This paper presents an experimental and numerical investigation of the flow control in an air intake S-shaped diffuser with and without energy promoters. The S-shaped diffuser had an area ratio 3.1and turning angle of 45°/45°. The proposed energy promoter was named as stream line sheet energy promoter. Computational Fluid Dynamics simulation was performed through commercial ANSYS-FLUENT 16.2 software. The measurements were made inside annular subsection, 45° from 360° of the complete annular shape of the diffuser, at Reynolds number 5.8×104 and turbulence intensity 4.1. Results for the bare S-shaped diffuser (without energy promoters) showed the flow structures within the S-shaped diffuser were dominated by counter-rotating vortices and boundary layer separation especially in the outer surface. The combination of the adverse pressure gradient at the first bend of outer surface and upstream low momentum wakes caused the boundary layer to separate early. The combinations of proposed energy promoters were installed on the inner and outer surfaces at three installation planes. The use of energy promoters resulting in significantly decreased the outer surface boundary layer separation with consequential improving the static pressure coefficient and reduction of total pressure losses. © The authors, published by EDP Sciences, 2017.